Regulation of oyster (Crassostrea virginica) hemocyte motility by the intracellular parasite Perkinsus marinus: A possible mechanism for host infection. Issue 78 (July 2018) - Lau, Yuk-Ting; Gambino, Laura; Santos, Bianca; Pales Espinosa, Emmanuelle; Allam, Bassem
Abstract: Hemocytes associated with the mucus lining of pallial (mantle, gill) surfaces of the oyster Crassostrea virginica have been recently suggested to facilitate infection by the Alveolate parasite Perkinsus marinus by mediating the uptake and dispersion of parasite cells. These "pallial hemocytes", which are directly exposed to microbes present in surrounding seawater, are able to migrate bi-directionally between mucosal surfaces and the circulatory system, potentially playing a sentinel role. Interestingly, P. marinus was shown to increase trans-epithelial migration of hemocytes suggesting it may regulate cell motility to favor infection establishment. The purpose of this study was to investigate the effect of P. marinus on hemocyte motility and identify specific molecular mechanisms potentially used by the parasite to regulate hemocyte migration. In a first series of experiments, various components of P. marinus (live P. marinus cells, extracellular products, fragments of P. marinus cell membrane, membrane-modified live P. marinus cells, heat-killed P. marinus ) along with components of the opportunistic bacterial pathogen Vibrio alginolyticus (bacterial cells and extracellular products) were investigated for their effects on hemocyte motility. In a second series of experiments, inhibitors of specific molecular pathways involved in motility regulation (Y-27632: inhibitor of Rho-associated protein kinase, RGDS: integrin inhibitor, CK-666: Arp2/3 inhibitor) were used in conjunction with qPCR gene expression experiments to identify pathways regulated by P. marinus exposure. Results showed a specific increase in hemocyte motility following exposure to live P. marinus cells. The increase in motility induced by P. marinus was suppressed by RGDS and CK-666 implicating the involvement of integrins and Arp2/3 in cell activation. Gene expression data suggest that Arp2/3 is possibly regulated directly by an effector produced by P. marinus . The implications of increased hemocyte motility prompted by P. marinus during the early stage of the infection process are discussed. Graphical abstract: Image 1 Highlights: Perkinsus marinus induces an increase of hemocyte migration in oyster. Hemocytes are chemoattracted to P. marinus . Enhanced motility is suppressed by RGDS and CK-666. Findings support the role of integrins and Arp2/3 pathways in motility regulation.